Association between dietary inflammatory indices (DII, EDII) and obesity with consideration of Insertion/Deletion Apo B polymorphism in type 2 diabetic patients. (September 2020) - Mokhtary, Nasim; Mousavi, Seyedeh Neda; Sotoudeh, Gity; Qorbani, Mostafa; Kalantar, Zahra; Koohdani, Fariba
Abstract: Purpose: Dietary inflammatory index (DII) and empirical dietary inflammatory index (EDII) are two indices that are used for studying the inflammatory score of diet. Inflammation is associated with obesity. Insertion/Deletion Apo B polymorphism is a candidate gene for susceptibility to obesity. The purpose of this study was to assess the association of DII and EDII with obesity with consideration of Ins/Del Apo B gene. Methods: In this cross-sectional study, 726 diabetic adults were included. DII and EDII were computed for each person based on validated food frequency questionnaire. Anthropometric values were measured. After extracting DNA by salting-out extraction method, Apo B Ins/Del was genotyped by PCR method and 8% polyacrylamide gel electrophoresis. Results: After adjustment for confounders no significant change observed in the comparison of DII and EDII tertiles about anthropometric measures and obesity. The same result was observed about interaction effect between dietary inflammatory indices and Insertion/Deletion Apo B polymorphism. Conclusions: We find no association between inflammation score of diet and obesity and no interaction effect between DII and EDII with Insertion/Deletion Apo B polymorphism on obesity. Further studies are needed to reach conclusive results. Highlights: Using 2 method include dietary inflammatory index (DII) and empirical dietary inflammatory index (EDII) for study obesity. Using both nutritional and genetic factors for study obesity. No association between diet inflammation and obesity was observed.